Effects of realistic pesticide mixtures on the springtail Folsomia candida - Tourinho, Paula S. (2025)
The application of multiple pesticides over the last decades has resulted in their frequent and in some cases long-term presence in soils as complex mixtures. This work assessed the toxicity of realistic pesticide mixtures to the springtail Folsomia candida observed in 11 case study sites. Each mixture was composed of five pesticides (as active substances or metabolites), chosen based on their occurrence in soil and expected risk to soil invertebrates. Reproduction tests were conducted in natural agricultural soil, and the springtails were exposed to three concentrations of the selected pesticides: the median environmental concentration (MEC), the predicted environmental concentration (PEC), and five times PEC (5PEC). No significant effect was observed at MEC exposure in any case study sites; however, effects on reproduction, adult survival, and adult size were observed at PEC and 5PEC exposures in five case study sites. Risk quotients (RQs) of individual pesticides were calculated by dividing the exposure concentrations (MEC, PEC, and 5PEC) by the no observed effect concentration values from the literature, and the sum of the five pesticides was calculated as ∑RQ in each case study site. The toxicity at PEC exposure was higher than expected based on the ∑RQ in two case study sites, indicating a possible synergistic mixture effect. This work provides new information on the effects of realistic pesticide mixtures. Further research is required to clarify whether the current risk assessment of individual pesticides adequately protects soil species from exposure to multiple pesticide residues that may occur in even more complex mixtures.